2021
DOI: 10.3390/membranes11080641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Alternating Magnetic Field towards Dispersion of α-Fe2O3/TiO2 Magnetic Filler in PPOdm Polymer for CO2/CH4 Gas Separation

Abstract: Magnetic-field-induced dispersion of magnetic fillers has been proven to improve the gas separation performance of mixed matrix membranes (MMMs). However, the magnetic field induced is usually in a horizontal or vertical direction. Limited study has been conducted on the effects of alternating magnetic field (AMF) direction towards the dispersion of particles. Thus, this work focuses on the incorporation and dispersion of ferromagnetic iron oxide–titanium (IV) dioxide (αFe2O3/TiO2) particles in a poly (2,6-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Histograms are also used to give an overview of the distribution of side lengths [9,21,23]. Some papers also calculate the areas and their statistics [23,24]. According to Bakshi et al [6] a higher mean and smaller standard deviation of the side lengths indicate better and more uniform distributions.…”
Section: Parametermentioning
confidence: 99%
“…Histograms are also used to give an overview of the distribution of side lengths [9,21,23]. Some papers also calculate the areas and their statistics [23,24]. According to Bakshi et al [6] a higher mean and smaller standard deviation of the side lengths indicate better and more uniform distributions.…”
Section: Parametermentioning
confidence: 99%
“…Magnetized MMMs display a relatively lower agglomeration size, increased degree of dispersion, and higher particle counts, along with higher selectivity than their unmagnetized counterparts. 18 However, there are other parameters such as alternating magnetic field (AMF) strength, magnetic field frequency, and magnetic field exposure time that influenced the dispersion of the nanoparticles. 16, 19 Spencer, Gao, and Yamamoto 19 showed that super paramagnetic iron oxide nanoparticles (SPION) assemble themselves through an oscillating magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The current work is an extension from the previous study and focuses on the mentioned parameters. 18 We fabricate α-Fe 2 O 3 /TiO 2 filler and incorporate it into a polymeric matrix to allow manipulation of its overall distribution via AMF. TiO 2 nanoparticles were used to pair with iron oxide in this study as they possess a high surface area to volume ratio, resulting in agglomeration to minimize their high surface energy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations